Low-cost and high-precision automobile front collision beam and preparation method thereof - XIAO LING; LI FAZHI; LI BIWEN; LIU ZHIWEN; CHEN JINGRAN; SUN KAIBO; CAO YUANLONG (2021)
The invention discloses a low-cost and high-precision automobile front collision beam and a preparation method thereof, and relates to the technical field of automobile parts. A low-cost and high-precision automobile front collision beam comprises a beam body. The cross beam body is an integrally-formed rectangular tubular component and comprises a middle arc-shaped section, transition sections connected to the two ends of the middle arc-shaped section and longitudinal beam connecting sections connected to the two ends of the transition sections. A method for preparing the low-cost and high-precision automobile front collision beam comprises the following steps: 1, carrying out extruding; 2, carrying out stretch bending; 3, carrying out stamping; 4, carrying out hole milling; and 5, assembling accessories. Compared with an existing automobile front collision beam, the manufacturing technological process is greatly simplified. On one hand, due to the fact that only one stamping procedure is carried out, only o